2004
DOI: 10.1038/sj.emboj.7600325
|View full text |Cite
|
Sign up to set email alerts
|

CD95 ligand induces motility and invasiveness of apoptosis-resistant tumor cells

Abstract: The apoptosis-inducing death receptor CD95 (APO-1/Fas) controls the homeostasis of many tissues. Despite its apoptotic potential, most human tumors are refractory to the cytotoxic effects of CD95 ligand. We now show that CD95 stimulation of multiple apoptosis-resistant tumor cells by CD95 ligand induces increased motility and invasiveness, a response much less efficiently triggered by TNFa or TRAIL. Three signaling pathways resulting in activation of NF-jB, Erk1/2 and caspase-8 were found to be important to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
297
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(312 citation statements)
references
References 52 publications
12
297
2
1
Order By: Relevance
“…Further studies are, however, required to investigate the FasL expression level in human tumors. Moreover, human tumors can also upregulate Fas expression by chemotherapeutic agents and the FasL expression in the apoptosis-resistant, Fas-expressed tumors increases their tumorigenicity by enhancing the motility and invasiveness through the Fas/ FasL interaction, 24 which extend the complexity of biological significance of the Fas/FasL interaction in human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are, however, required to investigate the FasL expression level in human tumors. Moreover, human tumors can also upregulate Fas expression by chemotherapeutic agents and the FasL expression in the apoptosis-resistant, Fas-expressed tumors increases their tumorigenicity by enhancing the motility and invasiveness through the Fas/ FasL interaction, 24 which extend the complexity of biological significance of the Fas/FasL interaction in human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after the discovery of the CD95 system, first reports appeared that CD95 stimulation does not always induce apoptosis but can also stimulate proliferation (e.g., in CD3-activated T cells) (Alderson et al 1993(Alderson et al , 1994(Alderson et al , 1995Desbarats et al 1999;Kennedy et al 1999), fibroblasts (Freiberg et al 1997), and hepatocytes following partial hepatectomy (Desbarats and Newell 2000). Intriguingly, certain cancer cells also responded to CD95 stimulation by increasing their proliferation (OwenSchaub et al 1993) or their motility and invasiveness (Barnhart et al 2004). Recently, Peter and colleagues found that the protumorigenic role of CD95 seems to be a more general principle across many cancers (Chen et al 2010).…”
Section: Physiological and Pathological Functions Of The Cd95 Systemmentioning
confidence: 99%
“…Upregulation of FasL expression is an early event in colon carcinogenesis Belluco et al, 2002), with tumour-expressed FasL being associated with apoptosis and loss of tumour-infiltrating lymphocytes (TIL) in vivo, and triggering the death of Fas-bearing sensitive cells in vitro (O'Connell et al, 1996;Okada et al, 2000). Engagement of Fas by FasL can also trigger proliferation of tumour cells (Lambert et al, 2003;Li et al, 2008) and increase tumour cell motility and invasiveness (Barnhart et al, 2004). Moreover, downregulation of FasL expression in colon tumour cells was recently shown to result in reduced tumour development and growth in immune-competent mice in vivo (Ryan et al, 2005).…”
mentioning
confidence: 99%